Tongxinluo preserves the renal function in diabetic kidney disease via protecting the HK-2 cells from the patterns of programmed cell death (Bangladesh Journal of Pharmacology, 2021)
This study was explored the renoprotective effect of Tongxinluo (a Traditional Chinese Medicine) on diabetic kidney disease and its underlying mechanism. The results revealed significant (p